Green Tea – An Herbal Drug: A Review - sharma, kavita (International Journal of Pharmaceutical & Biological Archive, 2010)
Green tea, produced from the plant Camellia sinensis is an affluent source of poly – phenolic compounds which are extremely beneficial against degenerative diseases like arthrosclerosis, Diabetes, Rheumatism, Parkinsonism, several cancer and has been used in Traditional system of medicine in many Asian countries. Epigallocatechin – 3 –gallate is the most abundant catachin found in green tea and plays a pivotal role in green tea medicinal properties. The potential health benefits ascribed to green tea include: antioxidant, cancer chemoprevention, improved cardiovascular health, anti-inflammatory, hepatoprotectant and immunomodulator.